Subtype distribution of Hepatitis C virus in Jiangsu, China. Issue 3 (31st August 2015) - Qi, Yinle; Chen, Qianqian; Hao, Fangyuan; Wan, Zhenzhou; Guo, Hongxiong; Lu, Renfei; Mao, Lingxiang; Du, Hong; Lu, Jian; Zhang, Chiyu
Abstract : Hepatitis C virus (HCV) genotype distribution varied by regions and transmission modes. In this study, we investigated HCV genotype distribution in five cities of Jiangsu, China, all of which are located in the Yangtze River Delta Region. A total of 363 samples were collected during 2011–2012. C/E2 and NS5B fragments of HCV were amplified using a multiple RT‐nested PCR strategy and subjected to sequencing. Phylogenetic analysis was performed for HCV genotyping. Among 106 PCR positive cases, HCV subtypes 1a (0.9%), 1b (61.3%), 2a (15.1%), 3a (4.7%), 3b (9.4%), 6a (6.6%), and 6n (1.9%) were detected. Together with our previous data, we found that HCV subtypes were more among injection drug users (IDUs) (nine) than among general population (GP) (six), and the most common subtype among GP was 1b (73.9%), followed by 2a (14.5%), while the top four common subtypes among IDUs were 3a, 1b, 3b, and 6a, with similar prevalence rates (24.4%, 22.7%, 20.9%, and 17.4%, respectively). There were nine HCV subtypes prevalent among IDUs in Jiangsu, more than those in Xinjiang, Hubei, Yunnan, Guangxi, Guangdong, and Hong Kong. The top four common subtypes among IDUs in Jiangsu covered all the two most common HCV subtypes (except 6n subtype) observed in six targeted provinces/region. These results suggested that Jiangsu may be an important gathering place for various HCV subtypes and the gathering may be involved in the large scale of population migration from other regions of China to Eastern China. J. Med. Virol. 88:498–505, 2016 . © 2015 Wiley Periodicals, Inc.